2016
DOI: 10.15243/jdmlm.2016.033.551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arbuscular mycorrhizal fungi on the potential of three wild plant species for phytoextraction of mercury from small-scale gold mine tailings

Abstract: Abstract:A study that was aimed to explore the effects of arbuscular mycorrhizal (AM) fungi inoculation on the potential of wild plant species (Paspalum conjugatum, Cyperus kyllingia, and Lindernia crustacea) for phytoextraction of mercury from small-scale gold mine tailings was conducted in a glasshouse. Each of the plant seedlings was planted in a plastic pot containing 10 kg of planting medium (mixture of tailings and compost; 50%: 50% by weight). Treatments tested were three plant species and doses of AM f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies showed that native AMF increased the growth of P. mooniana in greenhouse and nursery scale on inceptisol media (Husna et al 2015), serpentine (Husna et al 2016) and coal spoil (Husna et al 2019). In gold tailings media, native AMF is effective in increasing the growth of K. celebica (Husna et al 2019;, N. orientalis (Tuheteru et al 2020), Paspalum (Fiqri et al 2016), E. cladacalyx (Madejon et al 2012), and D. viscosa, A, eucomus and I. cylindrica (Orłowska et al 2011). Inoculation of 2 g AMF improved the growth of Pongamia pinnata plants in open pit coal mine soil media (Agus et al 2018).…”
Section: Mycorrhizal Colonization and Plant Growth In The Greenhousementioning
confidence: 99%
“…Previous studies showed that native AMF increased the growth of P. mooniana in greenhouse and nursery scale on inceptisol media (Husna et al 2015), serpentine (Husna et al 2016) and coal spoil (Husna et al 2019). In gold tailings media, native AMF is effective in increasing the growth of K. celebica (Husna et al 2019;, N. orientalis (Tuheteru et al 2020), Paspalum (Fiqri et al 2016), E. cladacalyx (Madejon et al 2012), and D. viscosa, A, eucomus and I. cylindrica (Orłowska et al 2011). Inoculation of 2 g AMF improved the growth of Pongamia pinnata plants in open pit coal mine soil media (Agus et al 2018).…”
Section: Mycorrhizal Colonization and Plant Growth In The Greenhousementioning
confidence: 99%
“…Several studies reported that certain AMF facilitate HM transport to aboveground plant organs (phytoextraction) (Bissonnette et al 2010;Fiqri et al 2016;Singh et al 2019). Other studies, however, revealed that AMF inhibit HM translocation by various means.…”
Section: Introductionmentioning
confidence: 99%
“…AMF is also potential to be developed as bioremediation agents (Simon et al, 2006; and in forest reclamation and restoration programs (Arshi et al, 2017;Maiti, 2013). In gold tailing ecosystem and mercury-contaminated soil media, AMF is beneficial for the vitality, growth and uptake of plant nutrients, as well as enhances the rebuilding of vegetation (Orłowska et al, 2011;Madejon et al, 2012;Fiqri et al, 2016;Husna et al, 2019;2020).…”
Section: Introductionmentioning
confidence: 99%